Fabrication of highly selective amine-cross-linked membrane for concentrated bio-succinate recovery from both synthetic model solutions and fermentation broth. (October 2020) - Zaman, Nadiah Khairul; Rohani, Rosiah; Mohammad, Abdul Wahab
Highlights: EDA-cross-linking of PI/GO membrane process replaced the imide with amine group. Cross-linking minimized the reduction in succinate rejection and selectivity. High membrane performances are sustained at increasing succinate concentration. Abstract: Reduced membrane rejection performance has been a big challenge for the membrane industry when dealing with concentrated complex feed solution. In this study, a robust mixed matrix membrane (MMM) of polyimide/graphene oxide (PI/GO) was systematically fabricated and modified using highly hydrophilic ethylenediamine (EDA) cross-linker under control conditions and tested for the recovery of succinate from fermentation broth at increasing feed concentration. The effects of membrane evaporation time (30, 45 and 60 s) and cross-linking time (0, 1 and 2 h) were investigated for achieving a membrane with inherent physicochemical properties of high succinate rejection and separation factor. The membrane was also tested for the recovery of succinate from by-products solution containing acetate and formate at increasing succinate concentration from 10 to 50 g/L. The result shows a successful cross-linking of PI/GO membrane using EDA with improved hydrophilicity. This is reflected in the reduced membrane contact angle and the increased membrane pure water flux to an average of 70% increase. At increasing feed solution from 10 to 50 g/L, the results showed that the cross-linking process reduced the dropped-in succinate rejection from 33 % for 1 h cross-linking time to 7% for 2 h cross-linking time compared to the non-cross-linked membrane of 73 % dropped-in succinate rejection. At 2 h cross-linking time, 91 % and 84 % succinate rejections were obtained for 10 and 50 g/L feed solutions, respectively. The improved succinate rejection was also reflected in the enhanced membrane selectivity performance. However, not much effect on succinate recovery was seen for the cross-linked membrane fabricated at a different evaporation time. This study herein introduces an alternative modification of cross-linking process on polymeric membrane in dealing with the enduring problem of reduced membrane performances when elevated succinate concentration was utilised.